Studi Cross-Textual Reading Terhadap Kisah Musa dan Panglima To Dilaling - Saputra, Jefri Andri (Jurnal Apokalupsis, 2023)
The background to this article is the leadership crisis in Indonesia. Before the 2024 general election, the author examines the characteristics of leaders who can realize people's welfare. The aim is to minimize leadership that makes people miserable. Then, the author examines the story of Panglima To Dilaling as text A and story of Musa as text B. The approach used is a cross-textual reading study. The story of Panglima To Dilaling and the story of Musa have several similar story motifs in the process of becoming a leader. A comparison of these two texts provides several characteristics of leaders who can overcome the leadership crisis and p rosper the community. Text A also provides several enriching interpretations of text B. The author finds that the story of Panglima To Dilaling enriches the story of Musa. Moses is able to free Israel because he received a call from God and because of his forgiving, sacrificial, and nurturing character. This character is the reflective material for choosing leaders.